2014
DOI: 10.1186/0717-6287-47-21
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids, sugars, vitamin C content and some pomological characteristics of eleven hawthorn species (Crataegus spp.) from Turkey

Abstract: BackgroundThe Hawthorn (Crateagus sp.) mostly occurs around the temperate region of the world with a high number of species, producing a fruit with numerous beneficial effects for human health. The aim of the study was to determine organic acid and sugar contents in the fruit of a number of hawthorn species grown in Erzincan province of Turkey.ResultsCitric acid was the predominant organic acid in all hawthorn species and C. pseudoheterophylla had the highest citric acid content (23.688 g/100 g). There were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 15 publications
3
59
0
2
Order By: Relevance
“…The seed number per fruit ranged from 1 to 4, agreeing with results of Gundogdu et al (2014). Seed stone length and width ranged from 6.15 to 8.89 and 4.63 to 6.98 mm, respectively, while stone weight varied from 0.27 to 0.56 g. Gundogdu et al (2014) observed that stone weight ranged from 0.13 to 0.75 g in hawthorn.…”
Section: Morphological Descriptionsupporting
confidence: 72%
See 4 more Smart Citations
“…The seed number per fruit ranged from 1 to 4, agreeing with results of Gundogdu et al (2014). Seed stone length and width ranged from 6.15 to 8.89 and 4.63 to 6.98 mm, respectively, while stone weight varied from 0.27 to 0.56 g. Gundogdu et al (2014) observed that stone weight ranged from 0.13 to 0.75 g in hawthorn.…”
Section: Morphological Descriptionsupporting
confidence: 72%
“…The current study is considered to be a valuable reference for forthcoming studies on morphological characteristics of the species to find the most favorable one to introduce it into for bring them commercial production. Similar level of diversity and similar intervals of variation for tree, flower, fruit, stone, and seed traits were found in different hawthorns evaluated (Guo and Jiao 1995;Asma and Birhanli 2003;Turkoglu et al 2004;Balta et al 2006;Yanar et al 2011;Gundogdu et al 2014). Finally, the studied accessions of C. monogyna could be recognized as representative gene pool and should be a priority for conservation action in Iran so as to maintain useful biodiversity.…”
Section: Cluster Analysis (Ca)mentioning
confidence: 85%
See 3 more Smart Citations